Implicações políticas, econômicas e socioambientais da RESEX Mãe Grande de Curuçá: perspectivas de desenvolvimento sustentável no estuário paraense? - BATISTA, Iane Maria da Silva (2015)
The political, economic and socio-environmental effects caused by the creation of the Marine Extractive Reserve of Mãe Grande de Curuçá-PA, on the local area and population, are diverse. The creation of the conservation unit in the municipality made it possible parmerships, interchanges, and agreements, as it engendered the implementation of public policies, directed toward the traditional population unta then historically excluded. However, despite advances, one verifies the persistence of unsustainable practices of management of the existing natural resources, as well as a correlation of unstable political forces which affects negatively the treatment of the existing socio environmental issues.